Hubungan peran ayah terhadap pemenuhan tugas perkembangan remaja - Erna Rahmawati; Rahmah Rahmah (Universitas Aisyiyah Yogyakarta, 2016)
Abstact: The research objective was to determine the relationshipbetween the father’s role on the fulfillment of tasks of adolescentdevelopment at MAN Yogyakarta I. This type of research is nonexperimentaland cross sectional approach. Samples taken by randomas many as 91 students. Data were collected using a questionnaire.Statistical test using the Spearman rank with significance level of p 0.05.The results showed that the adolescent developmental tasks most students59 respondents (64.8%) in the category enough. A father’s role most ofthe 45 respondents (49.5%) in both categories. Statistical analysis showedthere is a relationship to the father’s role in the fulfillment of tasks ofadolescent development MAN Yogyakarta I with r = 0.692 and p =0.000 (p 0.05).